Inventarisasi Jenis-Jenis Tumbuhan Tingkat Tinggi di Komplek Veteran Jalan Vetpur Raya I, II, dan III Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Ulfa, Syarifah Widya; Nabila, Mutiara; Nahombang, Syntia Zeyrani; Afrianti, Billah; Nayla, Nayla; Amalia, Qoyyum; Husnaa, Tsaabitah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to inventory and identify the types and diversity of higher plants in the Veteran Complex on Vetpur Raya I, II, and III streets in the Percut Sei Tuan District of Deli Serdang Regency, North Sumatra. Data was obtained through direct observation or field research on the characteristics of plants studied. The data collection technique uses observation, documentation, and literature methods. The results of the study show that there are 22 species of higher plants (Spermatophyta) in the area, consisting of Gymnospermae and Angiospermae. The Gymnospermae plants found in the Veteran Complex, Medan Estate, Percut Sei Tuan District, Deli Serdang Regency consist of 1 species from 1 family. Meanwhile, the Angiospermae plants found in the area consist of 18 species, consisting of monocot and dicot subclasses. Of these 18 species, 8 species consist of 7 families. Higher plants (Phanerogamae) are a group of plants that have seeds and reproduce sexually. The dominant higher plants Angiospermae in the Veteran Complex, Medan Estate, Percut Sei Tuan District, Deli Serdang Regency is the Zingiberaceae family, namely the species Alpinia galanga (galangal) which belongs to the herbaceous plant.